Association of urinary concentrations of phthalate metabolites with cardiometabolic risk factors and obesity in children and adolescents. (November 2018) - Amin, Mohammad Mehdi; Ebrahimpour, Karim; Parastar, Saeed; Shoshtari-Yeganeh, Bahareh; Hashemi, Majid; Mansourian, Marjan; Poursafa, Parinaz; Fallah, Zahra; Rafiei, Nasim; Kelishadi, Roya
Abstract: This study aimed to investigate the association of urinary concentration of phthalate metabolites with obesity and cardiometabolic risk factors in a pediatric population. This study was conducted in 2016 on 242 children and adolescents, aged 6–18 years, living in Isfahan, Iran. Urinary concentration of mono-butyl phthalate (MBP), mono-benzyl phthalate (MBzP), Mono-2-ethylhexyl phthalate (MEHP), Mono-methyl phthalate (MMP), Mono (2-ethyl-5-exohexyl) phthalate (MEOHP), and mono (2-ethyl-5hydroxyhexyl) phthalate (MEHHP) metabolites were determined. The association of these metabolites with obesity and cardiometabolic risk factors was examined using student t-test, linear and logistics regression tests. Of the 242 participants studied, 140 (57.9%) were girls and 102 (42.1%) were boys. The mean (SD) age of the population was 11.34 (2.55) years and no significant difference existed in terms of age ( p -value = 0.374). MBzP, MBP, MMP were observed in urine samples of all subjects, and MEHP, MEOHP, and MEHHP were observed in 99.6, 95.87, and 96.28% of the subjects, respectively. Of the total participants, 15.2% (n = 37) were obese and 37.7% (n = 92) were overweight. According to the logistic regression analysis, except MEOHP, all other pollutants were significantly associated with obesity (OR adjusted >1, p -value ≤ 0.002). A significant association existed between MBP and elevated blood pressure [OR crude in tertile3 = 4.87 (CI: 1.02–23.32), p-value = 0.024]. MBzP and MEHP were significantly associated with obesity, elevated levels of triglyceride and blood pressure. Increase in MBzP metabolite in the 3rd tertile resulted to about 2.5-fold increase in triglyceride levels than the first tertile [OR multivariate adjusted  = 2.7 (CI: 1.23–6.22)]. The findings of this study clearly showed the association between phthalate metabolites with obesity, cardiometabolic risk factors in children and adolescents, however further longitudinal studies are necessary to evaluate the clinical effects of this finding. Graphical abstract: Image Highlights: The urinary concentration of phthalate metabolites were determined. The association of these metabolites with cardiometabolic risk factors was examined. The amount of these metabolites in the studied population was very high. There was a relationship between these metabolites and cardiometabolic risk factors. Abstract : Capsule: The present findings demonstrated the association between urinary phthalate metabolites with obesity, some cardio-metabolic risk factors.